2009
DOI: 10.1111/j.1365-2982.2009.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

The nitric oxide synthase inhibitor, Ng‐nitro‐l‐arginine‐methyl‐ester, attenuates the delay in gastric emptying induced by hyperglycaemia in healthy humans

Abstract: The aim of this study was to determine whether the nitric oxide (NO) synthase inhibitor, N(g)-nitro-L-arginine-methyl-ester (L-NAME), reverses the effects of acute hyperglycaemia on gastric emptying and antropyloroduodenal (APD) motility. The study had a four-way randomized crossover (hyperglycaemia vs euglycaemia; L-NAME vs placebo) design in a clinical laboratory setting. Seven healthy volunteers [four males; age 30.3 +/- 3.8 years; body mass index (BMI) 23.6 +/- 1.2 kg m(-2)] were the study subjects. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…The magnitude of deceleration of emptying, the prolongation of the lag phase, and the slowing of the postlag emptying rate that we observed during hyperglycemia are consistent with these previous studies (20,22,23). Purported mechanisms governing this response include nitrergic pathways (24), direct stimulation of glucose-dependent neurons within the myenteric plexus (25), and suppression of vagal cholinergic activity, which has been demonstrated via reduced pancreatic polypeptide levels during hyperglycemia (26). Gastric emptying is the major ratelimiting step for glucose absorption from the gastrointestinal tract and therefore the primary determinant of postprandial glucose excursions (2,27).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The magnitude of deceleration of emptying, the prolongation of the lag phase, and the slowing of the postlag emptying rate that we observed during hyperglycemia are consistent with these previous studies (20,22,23). Purported mechanisms governing this response include nitrergic pathways (24), direct stimulation of glucose-dependent neurons within the myenteric plexus (25), and suppression of vagal cholinergic activity, which has been demonstrated via reduced pancreatic polypeptide levels during hyperglycemia (26). Gastric emptying is the major ratelimiting step for glucose absorption from the gastrointestinal tract and therefore the primary determinant of postprandial glucose excursions (2,27).…”
Section: Discussionsupporting
confidence: 79%
“…1). GLP-1 markedly increased the intravenous glucose required to maintain hyperglycemia (hyper/GLP-1 vs. hyper/placebo; Δ91 [24] g; P , 0.001) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…This appears, however, unlikely given that acute hyperglycemia has been shown to stimulate pyloric (13) and suppress antral (19) motility in the fasted state and that differences in distal stomach content were modest. The mechanism(s) mediating the effects of hyperglycemia on gastric motility are poorly defined but appear to involve nitric oxide pathways (34). Glucose-dependent neurons are also known to be present in the myenteric plexus (39) and central nervous system (44).…”
Section: Discussionmentioning
confidence: 99%
“…77 Other putative mediators of the effects of glycaemia on gastric emptying include ghrelin and nitric oxide. 78,79 Acute glycaemia-induced changes in gastric emptying have clear implications in the setting of the diagnosis of gastro paresis, and the effects of glycaemia need to be acknowledged. Unequivocal evidence has demonstrated that improved glycaemic control reduces microvascular, and probably macrovascular, complications of diabetes mellitus; 25,80 emerging evidence supports a similar improvement in gastric emptying and gastrointestinal symptoms following a major improvement in glycaemic control.…”
Section: Gastric Emptying and Glycaemiamentioning
confidence: 99%